Membangun Tata Kelola Klinis Melalui Clinical Pathway Demam Berdarah Dengue RSU Rizki Amalia Medika - Enuk Endah Sunarto (Universitas Muhammadiyah Yogyakarta, 2016)
In Rizki Amalia Medika Hospital there are variations in the treatment of patients with dengue haemorrhagic fever, so that it is requires better governance. This study is purposed to develop a clinical pathway of dengue haemorrhagic fever and to formulate clinical governance which are required to develop in Rizki Amalia Medika Hospital. This study is a qualitative research in Rizki Amalia Medika Hospital from September to November 2014. The data were obtained from medical records, standards of medical services and hospital reports, and interviews. The data analysis was performed with qualitative data analysis techniques. This research resulted in clinical pathways dengue fever based on the agreement of medical and paramedical staff in Rizki Amalia Medika Hospital, which is a template containing the information : a) the name of the patient, No. RM, date of birth, and special notes, b) information services every day for 6 days, c) variations in service with a date, reason and signature, d) the date of entry and exit, and e) the main diagnosis and the concomitant, accompanied ICD 10 code. Clinical pathway of dengue fever was used as the basis of examination and medical care of patients. This experiment also produced clinical governance which should be built in Rizki Amalia Medika Hospital among others: clinical audit activity, evidence-based clinical practice, and continuing education for medical staff. Clinical governance is necessary to achieve an appropriate health care standards.